THU0314 RELAPSES AND LONG-TERM REMISSION IN LARGE VESSEL GIANT CELL ARTERITIS IN NORTHERN ITALY: CHARACTERISTICS AND PREDICTORS IN A LONG-TERM FOLLOW-UP STUDY. (2nd June 2020) - Boiardi, L.; Muratore, F.; Restuccia, G.; Cavazza, A.; Catanoso, M. G.; Macchioni, P.; Spaggiari, L.; Cimino, L.; Aldigeri, R.; Pipitone, N.; Fontana, A.; Csaali, M.; et al.
Abstract : Background: Previous studies evaluated clinical relapses and long-term remission mainly in patients with biopsy-proven GCA and/or patients satisfying the ACR 1990 criteria for GCA classification. Also, radiological involvement was unfrequently used to define relapses and monitor disease activity in patients with LV-GCA Objectives: To evaluate characteristics and predictors of relapses and long-term remission in an Italian cohort of patients with large-vessel (LV) giant cell arteritis (GCA). Methods: We evaluated 87 consecutive patients with LV-GCA followed up at the Rheumatology Unit of Reggio Emilia Hospital (Italy) for at least 2 years. Patients with relapses and long-term remission were compared to those without. A comparison group of 34 patients with biopsy proven GCA without LV vasculitis (LVV) at diagnosis was considered for comparison. Results: 37 patients (42.5%) experienced one or more relapses. Nineteen (37.2%) of the 51 relapses were experienced during the first year after diagnosis. The majority of relapses occurred with doses of prednisone (PDN) ≤ 10 mg/day (74.5%). Polymyalgia rheumatica (PMR) (41.2%) and worsening at imaging of LVV (39.2%) were the most frequently observed relapsing manifestations. The total cumulative prednisone dose was significantly higher (p = 0.0001) and the total duration of PDN treatment longer (p = 0.0001) in relapsing patients compared to those without relapses. Relapsing patients had at diagnosis more frequently fever ≥ 38°C (p = 0.03) and visual manifestations (p = 0.03), and less frequently long-term remission (p = 0.003). In the multivariate model fever ≥ 38 °C (HR 3.22, 95%CI:1.43-7.27), duration of PDN treatment (HR 1.01, 95%CI: 1.00-1.02) and total cumulative PDN dose (HR 1.20, 95%CI: 1.09-1.33) were significantly associated with an increased risk of relapses, while aortic arch involvement at imaging at diagnosis (HR 0.22, 95%CI: 0.09-0.55) and long-term remission (HR 0.30, 95%CI: 0.12-0.75) with a reduced risk. 37 patients (42.5%) experienced long-term remission. PMR and disease relapses were less frequently observed (p = 0.003 for both), and the total cumulative prednisone dose was lower (p = 0.005) in patients with long-term remission compared to those without. In the multivariate model the presence of relapses (HR 0.33, 95%CI: 0.14-0.78) and the total cumulative PDN dose (HR 0.89, 95%CI: 0.83-0.96) were significantly negatively associated with long-term remission. Conclusion: In our cohort of patients with LV GCA we identified predictors of a relapsing course and long-term remission, which were observed in around half of the patients. Disclosure of Interests: luigi boiardi: None declared, Francesco Muratore: None declared, Giovanna Restuccia: None declared, Alberto Cavazza: None declared, Maria Grazia Catanoso: None declared, Pierluigi Macchioni: None declared, Lucia Spaggiari: None declared, Luca Cimino: None declared, Raffaella Aldigeri: None declared, Nicolò Pipitone: None declared, Antonio Fontana: None declared, Massimiliano Csaali: None declared, Stefania Croci: None declared, Nicolò Girolimetto: None declared, Carlo Salvarani Grant/research support from: consulting and investigator fees from Abbvie, Pfizer, MSD, Roche, Celgene, Novartis, Consultant of: consulting and investigator fees from Abbvie, Pfizer, MSD, Roche, Celgene, Novartis